A Review of the Literature on Patellar Tendinopathy: Current State of Knowledge - Jakub Milczarek; Błażej Szymczuk; Magdalena Iwan; Dominik Trojanowski; Ksawery Adamiec; Joanna Smorońska-Rypel; Małgorzata Rodak; Natalia Piątkowska; Magdalena Kajzar; Kamila Nitka (Nicolaus Copernicus University in Toruń, 2024)
Introduction: Patellar tendinopathy, commonly referred to as jumper's knee, presents as pain and dysfunction in the patellar tendon, predominantly affecting athletes engaged in jumping sports. The symptoms of patellar tendinopathy not only impact sports involvement but also interfere with activities of daily living, such as climbing stairs and sitting for extended periods, which in turn affects overall well-being. A variety of treatment options are available, encompassing both conservative approaches, such as modifying activity levels and undergoing physical therapy, and surgical methods. Aim of the study: The objective of this study is to review the current literature regarding the incidence, risk factors and currently available treatment methods for patellar tendinopathy. In addition, the aim is to present a summary of the knowledge and information collected so far in this area in a concise and accessible format. State of knowledge: The epidemiology and mechanisms of patellar tendinopathy are already well documented and described. The statistics regarding the incidence of patellar tendinopathy among athletes in the given fields are sufficiently consistent with each other. The existing literature provides insights into the efficacy of various therapeutic approaches for patellar tendinopathy, yet it is limited in scope. Conclusion: This review acknowledges that recent advancements in research have led to a fuller understanding of epidemiology and improvement of treatment methods for patellar tendinopathy. Despite this, a single therapy is not sufficient for optimal outcomes. Therefore, it is recommended that a comprehensive approach to conservative treatment be adopted. Further research and clinical trials are essential for the generation of reliable conclusions.